Pengaruh Sistem Reward dan Recognition terhadap Motivasi dan Kinerja Karyawan di Perusahaan Explore Wisata Organizer - Silviani Agustin (Syntax Corporation Indonesia, 2024)
This research aims to explore the influece of reward and recognition systems on employee motivation and performance at the Explore Wisata Organizer. Through a quantitative approach with survey methods, data is collected from employees to evaluate their perceptions of the reward and recognition system implemented. The results of the analysis show that the two systems have a significant impact on employee motivation and performance. These findings emphasize the importance of designing and implementing an effective reward and recognition system to improve performance in Explore Wisata Organizer companies.